CONTEMPORARY PERSPECTIVES IN THE EARLY DIAGNOSIS AND TREATMENT OF MALLORY-WEISS SYNDROME. (World Bulletin of Public Health, 2024)
Management of bleeding in Mallory-Weiss syndrome (MWS) remains a pressing problem in emergency surgery. According to some authors, MVS makes up 15% or more of bleeding from the upper gastrointestinal tract. In 80% of cases, MVS develops against the background of chronic liver and kidney diseases, chronic alcoholism, stomach and duodenal ulcers, chronic pancreatitis [2,5,27,33].